SOCIAL MEDIA, SOCIAL READERS: EXPLORING BOOKSTAGRAM’S IMPACT IN ROMANIA - Iuliana Obreja,; Adriana Manolică, (PEOPLE: International Journal of Social Sciences, 2025)
Online communities have begun to change how literature is discovered, discussed, and consumed, especially among younger readers. An increasing number of users are using #bookstagram on Instagram to express their literary interests and interact with like-minded people in Romania, especially now when the digital interactions are transforming the consumption patterns. This research investigates the influence of the Romanian bookstagram community on reading behavior, exploring how digital interactions impact readers' preferences, motives, and book selection processes. In order to achieve this, a qualitative research methodology was used, gathering detailed, daily reflections from active Romanian bookstagram users over time through the diary technique. This method allowed us to capture the nuances of individual experiences, emotional engagement with content, and the role of social interaction in shaping reading behavior associated with the #bookstagram hashtag. The findings suggest that the Romanian bookstagram trend is important for encouraging reading as well as for fostering a welcoming and visually appealing environment where book-related content becomes a form of self-expression and social bonding. By providing insights into how new media platforms are redefining conventional forms of literary engagement, this research adds to the expanding body of literature on digital cultural practices.